Analysis of oxygen-containing species in coal tar by comprehensive two-dimensional GC×GC-TOF and ESI FT-ICR mass spectrometry through a new subfraction separation method. (April 2022) - Zhu, Yonghong; Guo, Yuting; Teng, Haipeng; Liu, Jie; Tian, Feng; Cui, Louwei; Li, Wei; Liu, Jiaojiao; Wang, Chong; Li, Dong
Abstract: High oxygen content and ultracomplex composition are the biggest property characteristics of coal tar, which is also the biggest reason for the difficulty of coal tar separation and processing. The distribution of oxygen-containing compounds (OCs) and asphaltene island/archipelago structure play a key role in the solubility and hydrogenation thermal conversion of coal tar. In this study, the composition and structure of OCs in medium and low temperature coal tar (MLCT) and its subfractions were innovatively studied in the molecular level by GC × GC-TOF MS and negative ion ESI FT-ICR MS coupled with collision-induced dissociation (CID) through isolating a narrow mass-defined window based on the improved MLCT subfraction separation method. It revealed that the predominant OCs in MLCT are phenols with relatively few naphthols, furans, and ketones. The OCs are hugely dominated by O x species in aromatics, resins, and asphaltenes. The polyoxygenated OCs primarily exist in heavier components like asphaltenes. The O atoms prefer to be linked to the outsides of aromatic ring in the form of hydroxyl or carboxyl for low oxygen-containing compounds, and embedded in aromatic rings as the furan rings or cyclic ethers for multiple oxygen-containing compounds. Some O x species with a high H/C contain relatively smaller aromatic cores with more alkyl sidechains, which are the "atypical" molecules with multiple heteroatoms and low DBE in MLCT asphaltenes. Besides, the island-type structures are dominant for OCs in MLCT. The O x N n compounds have greater island attributes, especially for the molecules with multiple oxygen atoms. The MLCT asphaltenes contain more archipelago structure than that of aromatics and resins. The aromatic cores of OCs are not easy to be destroyed under the optimized voltage although the bridge bond breaking reaction occurs during CID. The heterolysis mode is absolutely the major bond cleavages path for OCs in MLCT. The heterolysis mechanism influences much on the generation of less-heteroatomic fragments, and the homolytic cleavage play a relatively important role during the generation of poly-heteroatomic fragments. Highlights: The composition of OCs in coal tar are studied by GC × GC-TOF MS and ESI FT-ICR MS through an improved separation method. The distribution of island and archipelago structural motifs in coal tar subfractions are obtained by qualitative method. The bond cleavage behaviors of OCs during CID are analyzed.